Alternatives and complements to POLCA system, in QRM cells configuration: simulated experiments - Gómez Paredes, Fernando José (2021)
The Paired-cell Overlapping Loops of Cards with Authorization (POLCA) is the Production Control System (PCS) that Quick Response Manufacturing (QRM) suggests for high variety and low volume. However, the suggested environment commonly describes the Make-to-order (MTO), which requires a PCS to control many routings of jobs, as the General Flow Shop (GFS) describes, and high variable lead times for each process. In those conditions, releasing orders by authorisation lists have presented some problems to deal with that time variability. One solution has been using alternatives PCSs as Control of Balance by Card-Based Navigation (COBACABANA). Another solution to that problem is that POLCA has incorporated other complements in the order release mechanism, as the Release-and-Flow POLCA (RF-POLCA), the Advanced Resource Planning and the COBA-POLCA. Nevertheless, those complements do not take advantage of the original concept of POLCA: the paired-cell overlapping loops. Therefore, this research proposes an order release mechanism based on the indirect load of a shop for POLCA, called IL-POLC, that uses the paired-cells loops to aggregate the indirect load. For that proposition, this research uses a systematic literature review to identify factors that influence how the PCSs work in the cited environment. Then, the research presents two simulation experiments to compare the IL-POLC proposed. The first experiment compares IL-POLC with the original POLCA and RF-POLCA, detailing specific factors for POLCA parametrisation. The second experiment compares IL-POLC with COBACABANA and COBA-POLCA. As a result of the literature review, this research presents a framework to describe how each factor influences the task of the PCSs. This framework was used to define factors in the experiments. The proposed IL-POLC shows that releasing jobs by indirect load conditions is better than the original order release of POLCA and RF-POLCA that uses the authorisation lists by release dates. IL-POLC solves the variability of lead times by the indirect load condition on the order release mechanism. According to the second experiment, IL-POLC is better than the other two PCSs when the shop uses the card-based version and a proportional representation of the card for the amount of work of each job. IL-POLC do not reduce the Shop Floor Throughput Time as the other systems, but it does not deteriorate the other performance measures. According to the results, the experiment suggests using IL-POLC in shops that it is challenging to estimate workload norms for the centralised release. Future research is suggested to confirm how the adapted order release reacts with external factors such as cell availability, labour interchangeability, and test in other scenarios as practical implementations to confirm these results.